2019
DOI: 10.1039/c8an01915k
|View full text |Cite
|
Sign up to set email alerts
|

Dual-binding pyridine and rhodamine B conjugate derivatives as fluorescent chemosensors for ferric ions in aqueous media and living cells

Abstract: Two new pyridine-type rhodamine B chemosensors (RBPO and RBPF) used to detect Fe3+ have been designed and synthesized, and the sensing behavior towards various metal ions was evaluated via UV–vis and fluorescence spectroscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The furan-2-carbonyl chloride modified rhodamine B derivative 36 selectively forms a complex with Fe 3+ in 1:1 ratio and shows significant fluorescence enhancement at 582 nm that allows to detect Fe 3+ down to 0.437 μM [44]. The pyridine-type rhodamine B fluorescent probes 37 and 38 are developed to detect Fe 3+ down to 0.067 μM and 0.345 μM, respectively [45]. Its analytical applicability has been tested by monitoring Fe 3+ concentrations in various real water samples and live cells.…”
Section: Fluorescent Turn-on Probes For Fe(iii)mentioning
confidence: 99%
“…The furan-2-carbonyl chloride modified rhodamine B derivative 36 selectively forms a complex with Fe 3+ in 1:1 ratio and shows significant fluorescence enhancement at 582 nm that allows to detect Fe 3+ down to 0.437 μM [44]. The pyridine-type rhodamine B fluorescent probes 37 and 38 are developed to detect Fe 3+ down to 0.067 μM and 0.345 μM, respectively [45]. Its analytical applicability has been tested by monitoring Fe 3+ concentrations in various real water samples and live cells.…”
Section: Fluorescent Turn-on Probes For Fe(iii)mentioning
confidence: 99%
“…This process severely interrupts the conjugation of space between O/N atoms or heterocycles, thereby quenching the fluorescence of PDPE-TO. 54–60…”
Section: Resultsmentioning
confidence: 99%
“…This process severely interrupts the conjugation of space between O/N atoms or heterocycles, thereby quenching the fluorescence of PDPE-TO. [54][55][56][57][58][59][60] In our experiments, we also investigated the nature of PDPE-TO fluorescence quenching by Fe 2+ ions using timeresolved fluorescence spectroscopy. Fig.…”
Section: Possible Quenching Mechanismmentioning
confidence: 99%
“…From Figure b, the maximum value of absorption of clip 1 ‐Fe 3+ appeared at 0.5268, which indicated that the stoichiometric ratio of the clip 1 ‐Fe 3+ is 1 : 1. The association constant was estimated to be 3.63×10 3 M −1 according to Benesi‐Hildebrand Formula (see supporting information): truenormalF-normalF0=[Fe3+](Fmax-F0)/(1/Knormala+[Fe3+]) …”
Section: Resultsmentioning
confidence: 99%